2017
DOI: 10.1111/ajd.12583
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use in dermatology for clinical photography and consultation: Current practice and the law

Abstract: Given the frequency of use and the degree of importance placed on the ability to send and receive clinical images, clinical smartphone use will persist and will likely increase over time. Current practices are insufficient to comply with professional and legal obligations, and increase practitioners' vulnerability to civil and disciplinary proceedings. Further education, realistic policies and adequate software resources are critical to ensure protection of patients, practitioners and the reputation of the der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 16 publications
6
81
1
1
Order By: Relevance
“…There are important efforts underway to develop standards and practices for dermatologic photography. The International Society of Digital Imaging of the Skin (ISDIS) recently published proposed technical guidelines, developed using Delphi consensus methodology . These guidelines address procedural standards of photograph acquisition, such as image lighting, orientation, field of view, background colour, resolution, depth of field and more.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are important efforts underway to develop standards and practices for dermatologic photography. The International Society of Digital Imaging of the Skin (ISDIS) recently published proposed technical guidelines, developed using Delphi consensus methodology . These guidelines address procedural standards of photograph acquisition, such as image lighting, orientation, field of view, background colour, resolution, depth of field and more.…”
mentioning
confidence: 99%
“…The International Society of Digital Imaging of the Skin (ISDIS) recently published proposed technical guidelines, developed using Delphi consensus methodology. [4][5][6][7] These guidelines address procedural standards of photograph acquisition, such as image lighting, orientation, field of view, background colour, resolution, depth of field and more. However, these guidelines do not address issues of patient consent, image storage and transmission, or the ethical and medico-legal implications of its use.…”
mentioning
confidence: 99%
“…Little is known about consumers’ views of mobile teledermoscopy and the factors that may affect consumers’ adoption of this technology. Most previous studies that explored acceptance of mobile teledermoscopy focused on clinician acceptance [5, 19-27]. …”
Section: Discussionmentioning
confidence: 99%
“…Materials and Methods and the corresponding Appendix, see www.karger.com/doi/10.1159/000493728) (Fig. 1) [19]. …”
Section: Methodsmentioning
confidence: 99%
“…While the abusive use of clinical photographs has become an increasing preoccupation of health fund organizations [75], only 30% of patients worry about the future of their photographs [76], and our review reported that only slightly more than half of the authors encrypted their data. While 60% of specialists continue to store photographs of their patients in their personal cell phones [74,[76][77][78][79], one perspective could be to develop recourse to encrypt the medical image libraries [66].…”
Section: Discussionmentioning
confidence: 99%